Attitude and Practices of self-medication among the students of Sialkot Medical College, Sialkot - Amara Sajjad, Sadia Majeed, Muammad Usman Rehman, Muhammad Sufyan Sarwar, Masooma Batool, Amber Ayoub, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: self-medication is becoming increasingly prevalent in our daily lives, yet it is a dangerous and harmful activity. Aim: To determine the prevalence and knowledge of self-medication among the medical students of Sialkot Medical College. Methods: A descriptive study in which total sample of 500 medical students were approached. Only, 349 students had filled the questionnaire. Regarding sampling technique, all the students currently enrolled in MBBS from session 2018 to 2022 of SMC were included. Data was collected using self-structured questionnaire. Data was analyzed using SPSS version 25. Results: Self-medication was found to be 83.8% during the last 1 year. Most commonly used medications include analgesic 73.2%, antibiotics 36.6%, gastric acidity medication 25.5%, anti-emetics and antitussives. Commonly experienced symptoms include; headache (73.6%), fever and flu (58%), cough (30.9%), gastric acidity (24.8%) and others. Source of information include family and friends (56.1%), medical text books (18.2%), internet (11.5%) and others. About 46.2% students felt that problem was not serious to consult a physician and 29% reported personal convenience. Conclusion: Prevalence of self-medication was high among the undergraduate university students of Sialkot Medical College, Sialkot. Keywords: Self-medication, prevalence, attitude